Composition of Targums after the Decline of Aramaic as a Spoken Language - Goṭlib, Leor (Aramaic studies, 2014)
The eighth century is the latest many scholars feel comfortable with for the use of Aramaic as a living language, before it was supplanted by Arabic. Therefore, clearly late Targums were usually dated circa the eighth century. However, persuasive arguments have been made in the past generation for a later dating regarding some Targums. This justifies a re-evaluation of the assumption that an Aramaic speaking environment is necessary for the continued composition of Targums. This article offers a possible Sitz im Leben for Targum composition after the decline of Aramaic as a spoken language throughout most of the Jewish world.